On anarchism - Chomsky, Noam. (New York ; London : The New Press, 2013)
"Radical linguist, philosopher, and activist Noam Chomsky is one of the world's foremost intellectuals. Known for his brilliant evisceration of American foreign policy, state capitalism, and the mainstream media, he remains a formidable and unapologetic critic of established authority. On Anarchism sheds a much-needed light on the foundations of Chomsky's thought, specifically his constant questioning of the legitimacy of entrenched power. The book gathers his essays and interviews to provide a short, accessible introduction to his distinctively optimistic brand of anarchism. Chomsky eloquently refutes the notion of anarchism as a fixed idea, suggesting that it is part of a living, evolving tradition, and he disputes the traditional fault lines between anarchism and socialism, emphasizing the power of collective, rather than individualist, action. Including a revealing new interview with Chomsky by well-known writer and blogger Nathan Schneider that assesses Chomsky's writings on anarchism to date, this is a book that is sure to challenge, provoke, and inspire. Profoundly relevant to our times, On Anarchism is a touchstone for political activists and anyone interested in deepening their understanding of anarchism and the man dubbed the "nation's conscience." Incorporating revealing interviews with Chomsky by writer Nathan Schneider that update each in light of today's events, this is a book that is sure to provoke and inspire. Profoundly relevant to our times, Chomsky on Anarchism is a touchstone for activists and anyone interested in politics and the man dubbed "our nation's conscience." "--
Notes on anarchism -- Exerpts from Understanding power -- Part II of "Objectivity and liberal scholarship" -- Interview with Harry Kreisler from "Political awakenings" -- Language and freedom.
Includes bibliographical references (pages 143-168).
Keywords: Anarchism -- History; Communism & Socialism